A Description of Handgrip Strength in the Very Older Adult People Living in Rural Vietnam and Its Association with Daily Functions. (9th July 2021) - Nguyen, Nga Thi Thuy; Nguyen, Thanh Xuan; Nguyen, Anh Trung; Nguyen, Thu Thi Hoai; Nguyen, Tam Ngoc; Nguyen, Huong Thi Thu; Nguyen, Huong Thi Thanh; Pham, Thang; Vu, Huyen Thi Thanh
Abstract : Objective . To describe handgrip strength (HGS) and identify associated factors in community-dwelling older adults in rural Vietnam. Methods . A cross-sectional study was conducted in community-dwelling older adults 80 years and over in five rural communities in Hanoi, Vietnam. Age-gender-BMI stratified HGS values were reported as means and standard deviations. Demographic characteristics, malnutrition, risk of fall, basic activities of daily living (ADL), and instrumental activities of daily living (IADL) were investigated. Multivariate linear regression explored the association between HGS and these factors. Results . In 308 participants, mean age was 85.4 ± 4.2 years. Mean HGS was 21.6 ± 6.1  kg for males and 15.3 ± 4.3  kg for females. HGS in our sample was generally lower than that in other European countries and Asian threshold. Low HGS was correlated with older age (β = − 0.196, p < 0.001 ), female (β = − 0.443, p < 0.001 ), low education (β = − 0.130, p < 0.05 ), risk of falls (β = − 0.114, p < 0.05 ), and lower IADL (β = 0.153, p = 0.001 ). Conclusions . The age-gender-BMI stratified HGS values of 80 years and over community-dwellers in rural Vietnam were described. HGS decreased with advanced age, female, low education, high risk of falls, and impaired IADLs. The results could provide useful reference data for further investigations and measures in clinical practice.